Psychological culture of the person in crisis society - Kohut, Alexandra (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The article is devoted to the study of models of personality adaptation in a crisis society in the aspect of development of psychological culture of personality.
Keywords: world; inner conflict; social anxiety; motives; spiritual values; meanings; experiences; ideas; harmonious development; social behaviours; personal growth; reflective thinking; areflexive contemplation